Analysis of the Factors in Influencing Students’ Willingness to Communicate in the Implementation Curriculum 2013 in English at Eleventh Grade of MAS Yati Kamang Mudiak - Ningsih, Yulia; Putri, Hilma Pami (Lembaga Yasin AlSys, 2023)
This research was due to discover Analysis of Students’ Factors in Influencing Willingness to Communicate in the Implementation Curriculum 2013 in English At Eleventh Grade of MAS Yati Kamang. This under graduated thesis aimed to find out dominant factors that influence students’ Willingness to Communicate (WTC) in the Implementation Curriculum 2013 at Eleventh grade of MAS Yati Kamang in Academic Year 2021/2022. It had been done at Eleventh Grade of MAS Yati Kamang because some students appeared to be hesitant to share their ideas. The other students seem nervous and not confident when the teacher asked students to raise their hands. Some students saw to avoid when the teacher ask them to go in front of the classroom using English. When the teacher asked one of students why the students were afraid come to the front of the class, and the students answered because they were afraid of being laughed by their friends and the students were afraid of being wrong. Hence, the researcher research about what were Students’ Factors in Influencing Willingness to Communicate in the Implementation Curriculum 2013 in English At Eleventh Grade of MAS Yati Kamang. The design of this research was qualitative research design. The key informants of the research were the Eleventh Students of MAS Yati Kamang, that consist of was 18 students. This research used observation checklist and interview to collect the data. The item of observation checlist was the item of environmental, individual dimension, linguistic dimension that consist of 22 items. In analyzing the data, the researcher used data reduction, data display, and drawing conclusion. Based on the results of the research, the researcher find out of the main Students’ Factors in Influencing Willingness to Communicate in the Implementation Curriculum 2013 in English At Eleventh Grade of MAS Yati Kamang. So, it concluded factors that influence students’ willingness to communicate was individual dimension. Hence, it indicated that individual dimension was factor dominant that supported students’ willingness to communicate.